SHELLS THAT HAVE BEEN POLLUTED BY LEAD AROUND YOUTEFA BAY IN JAYAPURA CITY THAT HAVE POTENTIAL RISK OF NON CARCINOGENIK - Hasmi Hasmi (UPT Penerbitan Universitas Jember)
According to several researchs, there are severalcoastal areas in Indonesia has contaminated withheavy metals, example lead. Lead contamination inwater can be found in the waters, bays, coastal,marine and rivers. Several reports found variety ofareas that had been contaminated with lead orplumbum (Pb) which exceeded the threshold valuewas allowed, even the impact of pollution. Forexample, lead pollutions in the Jakarta Bay (Fitriany, 2004; Sarjono, 2009; Rochyatun, 2003),the coastal of Riau (Nasution, 2011), Badung River(Bogoriani, 2006), coastal Borneo (Hartono, et all2011), Bali beaches (Nelyazar, 2007), and thecoastal of Makassar (Habrianti, 2013). In Papua,Youtefa bay in Jayapura is recorded as costal areasthat already contaminated Lead, and gulf youtefacan not be separated from the problem of heavymetal pollution because a part of ragtag Jayapura,the estuary into the gulf Yotefa. In 2004 (Arobaya& Pattiselano, 2010) a survey Bapedalda Jayapuraon water quality parameter Youtefa polluted sea ingulf of Pb has reached 0.03 mg/l. Based on theresearchresults Manalu in 2012, found that anindex ofpollution in the waters of the gulf of storetYoutefa based index (a value of raw data about thequality of the water which is then transformed intoan index ) are in moderate and severe polluted(Manalu, 2012).This study aims to analyze how much health risksthat caused by lead exposure in shells which mayeffect human health or community that stayaround this site. In addition, this researches isobservational research with risk analysisi or HazardQuotient. Samples have been collected throughpurposive sampling method.